1988
DOI: 10.1007/bf01535941
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of lactulose hydrogen breath test in subjects with normal or prolonged orocecal transit

Abstract: The within-subject repeatability of orocecal transit assessed with lactulose hydrogen breath test was evaluated in 15 healthy volunteers and 16 constipated or obese patients. The test was repeated twice in each subject. Mean (SD) transit time was 105 (63) and 103 (60) min in the first and second series of tests, respectively, showing that the first measurement did not affect the second. The within-subject repeatability of the test was related to the length of transit, the scatter of the differences between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In similar experimental conditions, the median orocaecal transit of 15 healthy volunteers was 80 min (range 40-170), and the coefficient of the within subjects repeatability, defined according to the British Standard Institution as two s.d.s of the mean difference between the first and the second test in the same subject, was 51 min (Camboni et al, 1988). …”
Section: Methodsmentioning
confidence: 99%
“…In similar experimental conditions, the median orocaecal transit of 15 healthy volunteers was 80 min (range 40-170), and the coefficient of the within subjects repeatability, defined according to the British Standard Institution as two s.d.s of the mean difference between the first and the second test in the same subject, was 51 min (Camboni et al, 1988). …”
Section: Methodsmentioning
confidence: 99%
“…The time between the ingestion of lactulose and the rise in breath hydrogen of at least 3, 5, or 10 parts per million (p.p.m.) above baseline, has been used to define the orocecal transit time (17,18). Validation studies have confirmed a high degree of correlation with simultaneous scintigraphy (19-22).…”
Section: Evaluation Of Small Bowel Transitmentioning
confidence: 99%
“…Accordingly, it is the relative rather than the absolute value of the transit time that is usually clinically important. When the reproducibility of the lactulose hydrogen breath test was investigated in three groups of subjects (normal, obese, and constipated), the transit time was 105 ± 63 min in the first test and 103 ± 60 min in the second test (8).…”
Section: Interpretation Of Lactulose Hydrogen Breath Test (Lhbt)mentioning
confidence: 99%